Zn-Ion Hybrid Micro-Supercapacitors with Ultrahigh Areal Energy Density and Long-Term Durability - Zhang, Panpan; Li, Yang; Wang, Gang; Wang, Faxing; Yang, Sheng; Zhu, Feng; Zhuang, Xiaodong; Schmidt, Oliver G.; Feng, Xinliang (Advanced Materials, 2019)
On-chip micro-supercapacitors (MSCs), as promising power candidates for microdevices, typically exhibit high power density, large charge/discharge rates, and long cycling lifetimes. However, as for most reported MSCs, the unsatisfactory areal energy density (<10 µWh cm−2) still hinders their practical applications. Herein, a new-type Zn-ion hybrid MSC with ultrahigh areal energy density and long-term durability is demonstrated. Benefiting from fast ion adsorption/desorption on the capacitor-type activated-carbon cathode and reversible Zn stripping/plating on the battery-type electrodeposited Zn-nanosheet anode, the fabricated Zn-ion hybrid MSCs exhibit remarkable areal capacitance of 1297 mF cm−2 at 0.16 mA cm−2 (259.4 F g−1 at a current density of 0.05 A g−1), landmark areal energy density (115.4 µWh cm−2 at 0.16 mW cm−2), and a superb cycling stability without noticeable decay after 10 000 cycles. This work will inspire the fabrication and development of new high-performance microenergy devices based on novel device design.
CRIS-Team Scopus Importer:2023-03-20
Keywords: durability; energy density; hybrid micro-supercapacitors; Zn-ion